A river cuts through it: the Métis on the two banks of the Ottawa River - Michel Bouchard; Sébastien Malette; Guillaume Marcotte (Journal de la Société des Américanistes)
The Métis of Canada were included as an Aboriginal people in the Constitution Act of 1982, but in the intervening decades we have observed a great disparity in the political and legal treatment of the various Métis communities by the federal and provincial governments. The Métis of the Ottawa River are a telling case, reflective of the disparities entrenched by the provincial border separating Ontario and Quebec. In chronicling the history of this particular Métis community, primarily through unpublished sources, we demonstrate that there is a shared Métis experience and identity in Canada, but that a contiguous community has been arbitrarily divided by a provincial boundary whereby the community is recognized on one side of the divide but not the other.